The Relationship Between Aggregation and Deformability of Red Blood Cells in Health and Disease - Lazari, Dan; Freitas Leal, Joames Kauffimann; Brock, Roland; Bosman, Giel (Frontiers in Physiology, 2020)
Tissue oxygenation depends not only on hemoglobin characteristics, but also on red blood cell characteristics such as metabolism, communication with the immune system, deformability and aggregability. Many if not all of these processes depend on the organization of the red blood cell membrane that enables the complex, dynamic interactions between the cell membrane and various intracellular and extracellular molecules. Studies of inborn errors of metabolism and membrane protein composition have paved the way for a membrane-centered molecular understanding of the factors that determine red blood cell function and survival, and of their role in cell morphology and membrane organization. However, little is known on the physiological and pathophysiological causes and consequences of interactions of the red blood cell membrane with extracellular components, such as the endothelial lining of the vasculature. Since this interaction is most prominent during red blood cell aggregation and deformation, we measured these properties in a variety of physiological as well as pathological conditions, i.e. during prolonged exercise, passage through a stand-alone circulation device, and during heart-lung machine-assisted cardiac surgery. Combined with data obtained with abnormally shaped red blood cells, our analyses indicate that: (1) various stress conditions affect aggregation and deformability; (2) changes in these parameters occur especially in the oldest cells; (3) both parameters are strongly correlated; (4) the decrease in this correlation for red blood cells with a disturbed membrane/cytoskeleton interaction indicates that there is a common molecular mechanism underlying aggregation and deformability characteristics.